Shopping American-Style: The Arrival of the Supermarket in Postwar Italy - Scarpellini, Emanuela (Enterprise & Society, 2004)
This article presents a case study of the establishment of the first Italian supermarket in 1957, carried out by an American industrial group called the International Basic Economy Corporation (IBEC). It raises the question of the export of a model born in the United States in a far different economic and political context. It was necessary to transform the technical and structural aspects of the supermarket as an institution to adapt to Italian society. This article also analyzes how other serious problems, deriving from the particular political and juridical situation of Italy, were confronted. In the end, the Italian supermarket was fundamentally different from the original model.
Keywords: Business History and gender